Factors Influencing Birth Preparedness in Rapti Municipality of Chitwan, Nepal - Kusmita Silwal; Jiwan Kumar Poudyal; Rajani Shah; Sumitra Parajuli; Yubanidhi Basaula; Sabika Munikar; Kanchan Thapa (Hindawi Limited, 2020)
Introduction. Birth preparedness is crucial for health quality of mother and newborn and acts as a strong contributor in mitigating maternal and newborn mortalities. Different factors are predicted to have an influence upon birth preparedness practice. This paper aims at exploring relationship between various factors and birth preparedness practice. Methods. A cross-sectional study design was used to find out the relationship between various factors and birth preparedness practice. One hundred sixty-five women residing at ward number 1 of Rapti Municipality, Chitwan who delivered in the last twelve months were selected consecutively and interviewed using a semistructured questionnaire. The collected data were analyzed using descriptive and bivariate techniques. Results. Three quarters (75.2%) of the respondents had better birth preparedness, institutional delivery was 63.0%, antenatal care (ANC) visit as per protocol was about 62.0%, and about 90% of the respondents had received counseling during ANC. Age, religion, family types, education, age at marriage, parity, number of children, knowledge on birth preparedness, knowledge on danger sign, place for ANC and delivery, and decision-makers were found to be statistically significant (P value < 0.05) with birth preparedness practice. Conclusion. Better knowledge on birth preparedness led to a better preparedness status. Age, religion, family type, education of women and partners, parity, and number of children were the factors that influence birth preparedness. Counseling during ANC played a significant role in birth preparedness.